2022
DOI: 10.1101/2022.06.21.496973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abl2 mediates microtubule nucleation and repair via tubulin co-condensation

Abstract: SummaryAbl family kinases are evolutionarily conserved regulators of cell migration and morphogenesis. Genetic experiments in Drosophila suggest that Abl family kinases interact functionally with microtubules to regulate axon guidance and neuronal morphogenesis. Vertebrate Abl2 binds to microtubules and promotes their plus-end elongation both in vitro and in cells, but the molecular mechanisms by which Abl2 regulates microtubule (MT) dynamics were unclear. We report here that Abl2 regulates MT assembly via con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Recently, it has been shown that condensed, liquid droplets of microtubule-associated proteins (MAPs), such as tau, TPX2, CAMPSAP2, and BuGZ, Abl2, and +Tip proteins, can form condensates via LLPS and nucleate microtubules when free tubulin is added to these condensates (21)(22)(23)(24)(25)(26)(27)(28). Tau is a good candidate for liquid-liquid phase separation (LLPS), since it is an intrinsically disordered protein (IDP) known to selfassociate (29,30), although it requires the addition of extra crowders to condense (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that condensed, liquid droplets of microtubule-associated proteins (MAPs), such as tau, TPX2, CAMPSAP2, and BuGZ, Abl2, and +Tip proteins, can form condensates via LLPS and nucleate microtubules when free tubulin is added to these condensates (21)(22)(23)(24)(25)(26)(27)(28). Tau is a good candidate for liquid-liquid phase separation (LLPS), since it is an intrinsically disordered protein (IDP) known to selfassociate (29,30), although it requires the addition of extra crowders to condense (22,23).…”
Section: Introductionmentioning
confidence: 99%